Believing without belonging? - Kardis, Mária (Bogoslovni vestnik, 2025)
The purpose of my paper1 is to present selected contemporary theories of religion in relation to modernity and late modernity. As well as their application in the Slovak social space. For this purpose, we will use the analysis of contemporary dates. Davie´s concept of “believing without belonging” has led to a number of interesting debates and discussions among scholars of religion and sociology. Some argue that this trend represents a decline in religious participation and an erosion of traditional religious values, while others see it as a positive development that allows for greater diversity and individual expression within religious and spiritual traditions. The aim of this article is to analyze the basic assumptions of Grace Davie’s concept and its application as a conceptual key to explain the transformation of religiosity in contemporary Slovakia, especially youth religiosity. The concept of “religion without obligation” is particularly applicable to the analysis of the dynamics and evolution of religiosity in contemporary Slovakia, especially among youth. The aim here will not be to discuss her works in detail, but only to present a few selected theses that seem relevant to the thought of the scholar in question. This article uses the method of content analysis and desk research.
Keywords: detradicionalizacija; detraditionalization; religiosity; religiosity of Slovak youth; religious identity; religious participation; religioznost; religioznost slovaške mladine; secularisation; sekularizacija; verska identiteta; verska udeležba